Movie Analysis : Punk Subculture Depicted in Punk in Love Movie - Lambok Hermanto Sihombing; Puji Lestari; Addina Isaputri (Celt: A Journal of Culture, English Language Teaching & Literature, 2021)
Abstract: Punk is subculture that has affected several aspects of life such as music, film or lifestyle. Punk has become part of Indonesian society. They are various point of view when society sees how the Punk is. Some people think that Punk is identical with rebellion and crime. On the other hand, some of them also think that Punk people are independent and always willing to help each other.  ‘Punk in Love’ is one of the movies that tried to show how Punk is. The researchers analyzed how Punk subculture was depicted in ‘Punk in Love’. In order to help the researchers doing the analysis, the researchers used the theory of Stuart Hall’s Representation. The data sources were taken from “Punk in Love” movie, websites, articles, and journals. The results of this study showed that Punk in ‘Punk in Love’ was portrayed as the community that has a strong solidarity. Keywords: movie, Punk, representation, solidarity, subculture Abstrak: Punk merupakan cabang kebudayaan yang telah memberikan pengaruh di beberapa aspek kehidupan seperti musik, film ataupun gaya hidup.  Punk telah menjadi bagian dari kehidupan bangsa Indonesia. Ada banyak sudut pandang ketika sesorang melihat apa arti Punk yang sebenarnya. Beberapa orang melihat bahwa Punk identik dengan pemberontakan dan kekerasan. Namun, sebagian dari mereka juga melihat bahwa Punk itu mandiri dan selalu berusaha untuk saling tolong-menolong. Film ‘Punk in Love’ merupakan salah satu film yang berusaha menampilkan bagaimanakah Punk itu. Dalam hal ini, penulis menganalisa cabang budaya Punk ini ditampilkan di film ‘Punk in Love’. Untuk membantu penulisan ini, penulis menggunakan teori Representasi dari Stuart Hall. Adapun sumber data penulisan ini diperoleh melalui film, websites, artikel, dan jurnal yang beruhungan dengan ‘Punk in Love’. Hasil penelitian ini menunjukkan bahwa Punk di dalam film ‘Punk in Love’ digambarkan sebagai komunitas yang memiliki solidaritas yang sangat kuat. Kata kunci: film, Punk, representasi, solidaritas, cabang budaya